Liikuntatuntien harjoitusmuotojen ja fyysisen aktiivisuuden määrän ja tason yhteydet oppilaiden viihtyvyyteen 9.-luokkalaisten kokemana - Luhtala, Helinä (2025)
Luhtala, H. 2025. The Connections Between Practice Styles and the Amount and Level of Physical Activity and Enjoyment in Physical Education Classes, as Experienced by 9th-Grade Students. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s Thesis in Sport Pedagogy, 40 pages, 3 appendices.